Sharea Issues in the Application of Takaful: Review on Islamic Law Perspective - Suharto Suharto; Muhammad Iqbal Fasa (Hunafa: Jurnal Studia Islamika, 2017)
Insurance is still debated between scholars when viewed in the light of Islamic law. Contemporary Muslim jurists are fully aware that the legal status of Insurance not been determined by Islamic law thinkers in advance (jurists). The application of Takāful today is the result of a struggle between the understanding of Islami law with the reality of what happened. Thus, the problem needs to be reviewed in the light of Islamic law in depth. This paper attempts to offer Shariah Issues in the Application of Takāful From Islamic Law Perspective, including The Concepts of Takāful (Sharia Insurance), Legal Basis of Takāful (Sharia Insurance), History of Takāful (Shariah Insurance) Development, Scholars' Views on Takāful (Sharia Insurance), The Principles of Takāful (Sharia Insurance), Establishment of Contract in Takāful (Sharia Insurance), and To Compare The Characteristics Between Takāful (Shariah Insurance) and Commercial Insurance.